Catalytic pyrolysis of petroleum sludge for production of hydrogen-enriched syngas. (14th December 2015) - Huang, Qunxing; Wang, Jun; Qiu, Kunzan; Pan, Zhijuan; Wang, Shoukang; Chi, Yong; Yan, Jianhua
Abstract: Petroleum sludge has attracted wide attention owing to its large quantity, hazardous character, and difficulty in processing. Furthermore, petroleum sludge contains a high proportion of hydrocarbons which are valuable for recovery. In this paper, the possibility of producing hydrogen-enriched syngas from different petroleum sludge by a two-stage catalytic pyrolysis under different temperature has been examined. X-ray photoelectron spectroscopy and C 13 nuclear magnetic resonance were employed to characterize the pyrolysis residues. The pyrolysis of three different petroleum sludge samples was discussed along with possible reaction mechanisms. It was found that heavy oil components vaporized in the first stage of pyrolysis. Thereafter, the gaseous compounds were cracked in the second catalytic stage forming H2, CH4, CO, and other small molecules. Higher catalytic temperatures can enhance the yield of H2 while lower temperatures would favor the generation of CH4 and CO. The pyrolysis of samples collected from a sludge storage tank gave the highest H2 yield (0.13 Nm 3 per kg sludge) among the three sludge samples examined. Additionally, after solid particles were removed by extraction (dissolution and centrifugation), catalytic pyrolysis produced 30% more H2 at 1000 °C. Finding of this paper indicates staged-catalytic pyrolysis is a promising method to convert hazardous petroleum sludge into high valuable syngas. Highlights: The feasibility of producing hydrogen enriched syngas from petroleum sludge is discussed. The heavy components in petroleum sludge will vaporize in the first pyrolysis stage. Gaseous compounds are cracked in the second stage to form small molecular gases. Higher catalytic temperature can enhance hydrogen yield. The removal of solid particles in the sludge will benefit hydrogen yield.